Effect of ingestion temperature on the pepsin-induced coagulation and the in vitro gastric digestion behavior of milk. (May 2023) - Yang, Mengxiao; Ye, Aiqian; Yang, Zhi; Everett, David W.; Gilbert, Elliot Paul; Singh, Harjinder
Abstract: Pepsin-induced protein coagulation occurs in the gastric environment when the milk pH is above the isoelectric point of casein proteins. In this study, the effect of milk temperature (4–48 °C) on the hydrolysis of κ-casein by pepsin and the consequent protein coagulation was studied at pH 6.0 for 120 min. Quantitative determination of the released para-κ-casein showed that both the κ-casein hydrolysis reaction rate constant and the pepsin denaturation rate constant increased with an increase in temperature. The temperature coefficient (Q10 ) of the specific hydrolysis of κ-casein was calculated to be ∼1.95. The coagulation process was investigated by the evolution of the storage modulus ( Gʹ ). At higher temperature, the milk coagulated faster but had a lower firming rate and Gʹ max with larger aggregates and voids were observed. The digestion behavior of the milk ingested at 4 °C, 37 °C, or 50 °C was investigated for 240 min in a human gastric simulator, in which the milk temperature increased or decreased to 37 °C (body temperature) over ∼ 60 min. The coagulation of the 4 °C milk was slower than for the 37 °C and 50 °C milk. The curd obtained from the 4 °C milk had a looser and softer structure with a significantly higher moisture content at the initial stage of digestion (20 min) which, in turn, facilitated the breakdown and hydrolysis of the caseins by pepsin. During the digestion, the curd structure became more cohesive, along with a decrease in moisture content. The knowledge gained from this study provides insight into the effect of temperature on the kinetics of pepsin-induced milk coagulation and the consequent digestion behavior. Graphical abstract: Image 1 Highlights: The temperature coefficient (Q10 ) of the specific hydrolysis of κ-casein is ∼1.95. The coagulation and microstructures of milk curd highly depends on the temperature. 4 °C milk coagulates slower during in vitro gastric digestion. 4 °C milk forms looser curd with higher moisture content after 20 min digestion. The hydrolysis of caseins by pepsin is faster in 4 °C milk curd.